Analisis Crowdfunding Syariah Berdasarkan Prinsip Syariah Compliance serta Implementasinya dalam Produk Perbankan Syariah - Novitarani, Anisah; Setyowati, Ro’fah (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
The presence of fintech in the form of crowdfunding with sharia principles can increase financing in Islamic banking. The concept of Islamic crowdfunding must basically be guided by the Qur'an and the Sunnah. This is in accordance with the Fatwa of the National Sharia Council-Indonesian Ulama Council (DSN-MUI) Number 117 / DSN-MUI / II / 2018. Referring to the Fatwa of the DSN-MUI, sharia crowdfunding in its implementation must be in accordance with Islamic law. The suitability of Islamic law with the concept of sharia crowdfunding can be seen from the perspective of shariah compliance, which must be free from gambling (maysÄ«r), usury (ribÄ), fraud (gharar) and wrongdoers (áº“Älim). Sharia crowdfunding can have at least two types of contracts in the transaction, musyÄrakah and qará¸. The two contracts must fulfill their respective terms and conditions so that the contract implemented can be considered valid. Problems that are often faced in implementing crowdfunding are in terms of legality and security. The problem of the law regarding the practice of sharia crowdfunding needs to be monitored by the National Sharia Board in order to conform to sharia so that people do not hesitate to invest through the sharia crowdfunding platform.